Skærsildens rum og sjælens rolle. Rumlig iscenesættelse og individuel agens i middelalderens forestillinger om skærsilden - la Cour, Elias Due (Historisk Tidsskrift, 2025)
Spatial Models of Agency in Medieval Visions of Purgatory This article examines how medieval visions of Purgatory represent the soul’s agency in the process of postmortal purification. Through readings of six vision texts from the 12th to 14th centuries - including works by Hildegard of Bingen, Dante Alighieri’s Purgatorio, and Visio Godeschalci - the article analyses how spatial structures in the afterlife both reflect and condition the soul’s involvement. Instead of treating Purgatory as a fixed theological category, the article approaches it as a literary and spatial phenomenon, where landscapes of trial and transition shape types of agency. In these visions, the soul is not merely subject to divine judgment but must act, decide, and orient itself within purgatorial space. Agency takes multiple forms - physical movement, moral discernment, ritual engagement - and becomes integral to the logic of salvation. The article argues that purgatorial space is not portrayed as a static or predetermined realm, but as a dynamic field of interaction, in which purification depends on the soul’s ability to respond, persevere, and participate.